Profil indeks massa tubuh dan daya tahan kardiovaskular (VO₂Max) peserta ekstrakurikuler futsal Sekolah Menengah Atas - Roihan Hafizh Muzakki; Hariyoko Hariyoko (Motion: Journal Research of Physical Education, 2023)
Futsal is a sport that is included in the physical activity category of strenuous sports that are dynamic. To produce quality players must pay attention to one of them body mass index. In addition, good cardiovascular endurance must be possessed, because it affects as a support for players in the game. Based on the description presented, it is very important to know the profile of body mass index and cardiovascular endurance to be an evaluation material and to support performance. This study aims to determine and examine the profile of body mass index and cardiovascular endurance of futsal extracurricular participants of Public High School 1 Rejoso. This study used quantitative descriptive type survey method. The population in this study numbered 40 with 20 participants taken as samples. Based on the measurement results, the body mass index results of futsal extracurricular participants were 3 participants (15%) in the category of severe underweight, 3 participants (15%) in the category of light underweight, 13 participants (65%) in the ideal weight category and 1 participant (5%) in the category of light overweight. While the cardiovascular endurance of 10 participants (50%) belonged to the very deficient category, 7 participants (35%) the less category, and 3 participants (15%) the moderate category. Thus, it can be concluded that body mass index is classified as an ideal weight category while cardiovascular endurance is classified as a very less category.